Dampak Pembiayaan Defisit Anggaran dengan Utang Luar Negeri terhadap Inflasi dan Pertumbuhan Ekonomi: Studi Kasus Indonesia Tahun 1970-2003 - Waluyo, Joko (UI Scholars Hub, 2006)
The main purpose of this study is to find the effect of budget deficit with foreign loans as source of funding on inflation and economic growth. This study focuses on transmission mechanism of budget deficit funding effects on inflation and economic growth. We use a specific simultaneous macroeconomic model which includes 17 behavioral equations and 18 identity equations with 6 blocks in this study, Two Stage least Square (TSLS) method is employed to estimate the behavioral equations in the model. This study use Indonesia secondary economic data from 1970 to 2003. Econometric tests are performed to produce BLUE estimator. This study also use stochastic simulation with 10.000 replications to simulate policy. The results show that using foreign loan to fund budget deficit increases both economic growth and inflation. This result is also supported by the simulation results which show that increase in the proceeds of new foreign loan increases reserves which in turn increase primary money/money supply/monetary base. Interaction of monetary base with money multiplier then increases price level. Increase in capital inflow from increase in foreign loan in reases government spending which also increases government spending. Increases in the government spending then add to government capital stock so that economic growth also increases.